Analisis Besaran Tambahan Penghasilan Pegawai Bedasarkan Kelas Jabatan bagi PNS/CPNS Pemerintah Provinsi Sumatera Selatan - Irawati, Septiana; Hendarso, Yoyok; Nugraha, Mega (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the amount of additional employee income based on position class for civil servants/CPNS in the South Sumatra Provincial Government. The research method used is descriptive qualitative with an inductive approach which focuses on observations or observations first, then continues with drawing conclusions. The results of the analysis show that the policy of providing additional employees in the Sumatra Province does not violate Law Number 1 of 2022, this is because it does not exceed the maximum limit of the provisions stipulated in this regulation, namely 30% of the total APBD expenditure. The percentage of government personnel expenditure is only 20.85%; which means that the policy on the amount of Additional Employee Income (TPP) within the South Sumatra Provincial Government should not interfere with other development budget allocations. However, this research found the fact that the payment of additional income towards the end of the year was delayed, and the productivity of the regional government of South Sumatra Province in regional development decreased, this was closely related to regional budget limitations caused by the regional expenditure ceiling being larger than the regional income ceiling.